TUNGKU KRUSIBEL DENGAN ECONOMIZER UNTUK PRAKTIK PENGECORAN DI JURUSAN PENDIDIKAN TEKNIK MESIN FT UNY - Arianto Leman Soemowidagdo (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
This research was aimed at developing economizer on aluminium crucible furnace to improve its performance. Research and Development method was implement. The economizer effects was determined from the performance test. Furnace tested without and with economizer at the same process condition. The furnace exhaust developed has same diameter with the gas burner inlet. The exhaust was extended and deflected serves as an economizer. Aluminum of 11.78 kg can be melted with an economizer in 60 minutes and requires 2.6 kg LPG, while without economizer it was require 3.1 kg LPG and 80 minutes.